Considerations regarding the unconstitutionality of articles 55¹ and 99¹ of the law on local public administration - Mihai Cristian Apostolache; Mihaela Adina Apostolache (Juridical Tribune, 2017)
Since its entry into force and to date, Law no. 215/2001 on local public administration has undergone many amendments and completions. One of the questionable additions to this act is done by GEO (OUG) no. 41/2015, a regulation which brought two new articles to the body of the framework-law on local public administration, i.e. Article 55¹ and Article 99¹. These two articles regulate a unique way of establishing the local or county council, namely by reconstituting these autonomous collegial bodies. This article examines the legislative intervention made by GEO no. 41/2015 and highlights the unconstitutionality aspects of this legislative intervention, recommending the legislature to urgently repeal the regulations governing the reconstitution of the local and county councils.